Academic Resilience of Lecturers at State and Private Islamic Universities During the Pandemic: Meaning, Adaptation, and Innovation - Khalilah Khalilah (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This article aims to discuss the meaning of academic resilience by lecturers who worked for the Indonesian State and Private Islamic Universities and modes of adaptations and innovations taken by these lecturers to increase their academic resiliences when they carried out the higher education’s tri-dharma. The survey data collected from 37 lecturers employed by such Islamic universities using an online survey. Quesioners written in a google form was distributed via WhatsApp to all lecturers’ network associated with these universities. The findings are as follows. Respondents define academic resilience as the ability to adjust in the face of obstacles and demands throughout the learning and teaching process in a demanding setting. Only a tiny percentage of respondents saw academic resilience as related to students' ability to adapt to challenges and pressures during the learning process in a demanding environment. Most respondents perceived a need to adapt and innovate in higher education tri-dharma activities, academic administration services, and resource management supporting academic activities. Most respondents also rated the significance of personal and professional factors contributing to academic resilience as a teacher.